Consumer Health Perception of Seafood Related to Customer Attention to Seafood-Eco Labels in purchase decision in Indonesia - Panji G Prasetya; Katarina Joan; Irfan Byna Nur Akbar; Asdrin Qiranne (Jurnal Pijar, 2023)
Purpose - The purpose of this study was to examine the role of consumer health perceptions of seafood in relation to consumer attention to environmentally friendly seafood labels in Indonesia when making purchasing decisions. Based on the previous literature, three variables have been considered for this study, which are as follows: awareness and interest in eco-labels, altruistic values, and socio-demographic and cultural factors. Design/Methodology/Approach - Data was collected using a questionnaire distributed randomly in Indonesia. A total of 301 valid respondents were obtained after passing through filter questions, where responses were recorded on a seven-point anchor Likert-type scale where 1 indicated strongly disagree and 7 indicated strongly agree. Then, the analysis was carried out using Exploratory Factor Analysis and Multiple Regression Analysis. Findings - In contrast with findings from the primary journal reference, our study found that people with higher level education appear not to have interest in eco-labels. On the other hand, people with altruistic behavior who perceive seafood that is caught or farmed in a sustainable manner can contribute positively to the environment and workers are keen to understand about ecolabels. In Indonesia, awareness and consumers’ health perception are the two factors that have the most impeccable influence on eco-label. This finding is quite the opposite of the results in Spain and Italy where level of education and altruism are the most significant factors. Age of influence - Research Limitations: Most of respondents are not familiar with seafood eco-labels. Practical Implication - Stakeholders in marketing may realign their strategies by creating certain information tools such as logos that can increase consumer’s attention to ecolabels as well as using green attributes as part of their marine sustainable movement to cater the needs of consumers with altruistic values. In addition, the Government can also take a step to educate the importance of marine ecosystem and wellbeing, sustainable fisheries and responsible resourcing. Originality/value - This study is one of the few studies that discusses research on purchase intentions of environmentally friendly seafood in developing countries. Keywords - Environmentally Friendly Seafood, Seafood Eco-Label, Consumer Health Perception, Purchase Decision, Consumer Attention, Multiple Regression Analysis Paper Type - Research Paper